Generator‐based threshold for transient stability assessment. Issue 3 (7th June 2019) - Isbeih, Younes J.; El Moursi, Mohamed Shawky; Xiao, Weidong; El‐Saadany, Ehab
Abstract : Power systems are frequently subjected to variations of the operating conditions due to the occurrence of contingencies such as faults, load or generator tripping. These disturbances might enforce the system to enter the instability region and thus deteriorate its overall performance. This paper proposes a systematic approach for transient stability assessment using generator‐based threshold. An individual stability limit is designed for each generator instead of using only one pre‐defined threshold for all generators. The considered contingencies are characterized by a fault type, location, loading condition and critical clearing time to consider wide range of operating conditions. Two fault locations are only considered to reduce the search space for stability limits; the generator terminals and mid of transmission lines. The critical clearing time is used to find the maximum relative rotor angle (MRRA) of individual generators attained during the entire time domain simulation. The MRRA of each generator represents the maximum angle which can be reached without losing synchronism at a given contingency. Conservative stability limits are drawn around the minimum stable drift of each generator which is chosen from the set of MRRAs of all contingencies. The effectiveness of the proposed approach is tested using the modified New‐England, 39‐bus system.